Evaluating Public and Private Transport of Lahore - Iqbal, Rahat; Urfan Ullah, Muhammad; Habib, Ghulam; Kaleem Ullah, Muhammad (Riviera Publishing, 2023)
The growth of urbanization, as a result, has led to a higher number of motor vehicles, due to which there has been a considerable increase in traffic volumes in recent years. The existing road capacity and service levels do not fully meet the current needs of commuter traffic and transport. Along with providing fixed route services, transit systems integrated with these services have become a necessity for the community. The research design includes selecting a case study area, Lahore. The means of systemization that have been adopted to achieve the objectives of the research carried out include topic selection, comprehensive literature review in the context of local and international scenarios, data collection covering primary and secondary, data analysis using Excel and SPSS software, interpretation of data and placement of appropriate proposals. The main result of this study is that by improving public transport safety and public transport management, people's preference for using public transport will increase. Also, public transport's cleanliness and service level will increase; hence, the preference for using public transport will increase. The research's recommended solution for the city of Lahore has been designed locally to meet the majority problem, as the solution must be low-cost, environmentally sustainable, and responsive to the social demands of the local community.